Different Effects of Cyclical Ketogenic vs. Nutritionally Balanced Reduction Diet on Serum Concentrations of Myokines in Healthy Young Males Undergoing Combined Resistance/Aerobic Training - Kysel, Pavel; Haluzíková, Denisa; Pleyerová, Iveta; Řezníčková, Kateřina; Laňková, Ivana; Lacinová, Zdeňka; Havrlantová, Tereza; Mráz, Miloš; Kasperová, Barbora Judita; Kovářová, Viktorie; Thieme, Lenka; Trnovská, Jaroslava; et al. (Nutrients, 2023)
Myokines represent important regulators of muscle metabolism. Our study aimed to explore the effects of a cyclical ketogenic reduction diet (CKD) vs. a nutritionally balanced reduction diet (RD) combined with regular resistance/aerobic training in healthy young males on serum concentrations of myokines and their potential role in changes in physical fitness. Twenty-five subjects undergoing regular resistance/aerobic training were randomized to the CKD (n = 13) or RD (n = 12) groups. Anthropometric and spiroergometric parameters, muscle strength, biochemical parameters, and serum concentrations of myokines and cytokines were assessed at baseline and after 8 weeks of intervention. Both diets reduced body weight, body fat, and BMI. Muscle strength and endurance performance were improved only by RD. Increased musclin (32.9 pg/mL vs. 74.5 pg/mL, p = 0.028) and decreased osteonectin levels (562 pg/mL vs. 511 pg/mL, p = 0.023) were observed in RD but not in the CKD group. In contrast, decreased levels of FGF21 (181 pg/mL vs. 86.4 pg/mL, p = 0.003) were found in the CKD group only. Other tested myokines and cytokines were not significantly affected by the intervention. Our data suggest that changes in systemic osteonectin and musclin levels could contribute to improved muscle strength and endurance performance and partially explain the differential effects of CKD and RD on physical fitness.
Keywords: ketogenní dieta; cytokines; svalová síla; Resistance Training; adipokines; ketogenic diet; Renal Insufficiency, Chronic; chronická renální insuficience; cytokiny; mužské pohlaví; Cytokines; redukční dieta; složení těla; Muscle Strength; odporový trénink; osteonektin; endurance; Humans; myokines; training; Osteonectin; body composition; Diet, Ketogenic; strength parameters; Body Composition; Diet, Reducing; lidé; Male